Practical Recommendations on Laboratory Monitoring in Patients with Atopic Dermatitis on Oral JAK Inhibitors - Mark G. Kirchhof; Vimal H. Prajapati; Melinda Gooderham; Chih-ho Hong; Charles W. Lynde; Catherine Maari; Irina Turchin; Kim A. Papp (Adis, Springer Healthcare, 2024)
Abstract Oral Janus kinase inhibitors (JAKi), a class of advanced targeted systemic therapy, have demonstrated efficacy and safety in the treatment of moderate-to-severe atopic dermatitis (AD). Like other small molecules, oral JAKi have the potential for off-target effects including laboratory-related adverse events (AEs). Product labels for oral JAKi recommend an initial laboratory assessment and follow-up 4-12 weeks later to monitor for potential changes, based on evidence from clinical trials across therapeutic indications for oral JAKi, which may not reflect a population of moderate-to-severe AD patients typically seen in routine clinical practice. To address this gap, a panel of eight dermatologists with clinical and research experience with oral JAKi for the management of AD conducted a targeted review of the literature focused on key laboratory-related AEs associated with oral JAKi in the moderate-to-severe AD population. Based on the synthesis of evidence and informed opinion, a set of best practice statements related to fundamental standards of care and consensus recommendations on laboratory monitoring were suggested, and level of agreement was ascertained using a Likert scale from 0 to 100. There was a high level of agreement on three of the four suggested recommendations related to assessment and monitoring of key laboratory parameters and to dose reduction or switching in response to laboratory changes; there was a lower level of agreement related to the frequency of ongoing laboratory monitoring. Appropriate patient selection and laboratory assessment is an important strategy to mitigate the potential risks associated with oral JAKi when treating AD.